2017
DOI: 10.1139/cjes-2016-0146
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally altered volcanic rocks metamorphosed at granulite-facies conditions: an example from the Grenville Province

Abstract: A 1.2 Ga association of aluminous gneisses, garnetites, and white felsic gneisses of andesitic composition in the southern Manicouagan area (central Grenville Province) provides evidence consistent with protolith formation and hydrothermal alteration in a submarine volcanic environment. In addition to field relations, potential relics of quartz phenocrysts in the aluminous gneisses, revealed by SEM–MLA (scanning electron microscope with a mineral liberation analysis software) imaging, are consistent with a vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Spessartine garnet porphyroblasts have been observed in hanging-wall and footwall strata surrounding VHMS mineralization in the Yilgarn Craton at Hollandaire and Wheatley (Hayman et al 2015;Hassan, 2017a). Elevated contents of Mn in garnet from garnetites, and Zn in spinel from aluminous gneisses were recently noted from granulite-facies rocks in the central Grenville Province, Canada, highlighting its potential for VHMS mineralization (Hindemith et al 2017). Corriveau and Spry (2014) have further suggested that staurolite becomes increasingly orange with Zn content.…”
Section: Vectors and Halos To Mineralizationmentioning
confidence: 99%
“…Spessartine garnet porphyroblasts have been observed in hanging-wall and footwall strata surrounding VHMS mineralization in the Yilgarn Craton at Hollandaire and Wheatley (Hayman et al 2015;Hassan, 2017a). Elevated contents of Mn in garnet from garnetites, and Zn in spinel from aluminous gneisses were recently noted from granulite-facies rocks in the central Grenville Province, Canada, highlighting its potential for VHMS mineralization (Hindemith et al 2017). Corriveau and Spry (2014) have further suggested that staurolite becomes increasingly orange with Zn content.…”
Section: Vectors and Halos To Mineralizationmentioning
confidence: 99%